Bombus lucorum - Pauly, Alain (Zenodo, 2018)
Bombus lucorum (Linné, 1761) 17.VII.1978, 1D, Campanula rotundifolia 21.VII.2013, 1D, lande, fauchoir talus. Published as part of Pauly, Alain, 2018, Les abeilles sauvages de la lande de Streupas (Hymenoptera: Apoidea), pp. 1-36 in Belgian Journal of Entomology 60 on page 20, DOI: 10.5281/zenodo.13619251